PENINGKATAN KUALITAS MAKHORIJUL HURUF MELALUI PROGRAM MUROJA’AH KLASIKAL DI PONDOK PESANTREN PUTRI WALISONGO CUKIR DIWEK JOMBANG - Alsakina, Sahara Queen; Surur, Shobihus; Arini, Aida (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2024)
This exploration discusses perfecting the quality of makhorijul letters through the classicalmuroja'ah program at the Putri Walisongo Islamic boarding academy. An preceptor isn't only needed to understand or master a number of literacy accoutrements that he'll convey to actors, but he must master a number of literacy styles and ways in order to continue the metamorphosis of literacy accoutrements and understand each pupil's psychology. A literacy system or model will impact whether or not the material or information is good for scholars. The end of this exploration is to determine the enhancement in the quality of makhorijul lettersthrough the classicalmuroja'ah program at the Putri Walisongo Islamic residential school. This exploration employes a qualitative methodology using qualitative exploration styles. Meanwhile, the type of exploration used is qualitative description exploration. Three methods are used to acquire data: documentation, interviews, and observation.The outcome of this exploration demonstrate that perfecting the Quality of Makhorijul Letters at the Putri Walisongo Islamic Boarding School has several situations, videlicet intelligence, interest and gift, provocation. The classical Muroja'ah program at the Putri Walisongo Islamic boarding academy is a literacy program that aims to repeat memorization with tartil and use applicable makhorijul letters and enumeration styles. perfecting the quality of makhorijul letters through the classicalmuroja'ah program at the Putri Walisongo Islamic boarding academy is getting better and there are stages of achievement for the scholars. From the morning, scholars who could not do it at all came suitable and understood how to gasp makhroj duly and rightly. There are supporting factors, videlicet provocation, targets, intentions, inhibiting factors, videlicet scholars' lack of attention, shiftlessness.